"So Happy I Could Shout!" and "So Happy I Could Cry!" Dimorphous expressions represent and communicate motivational aspects of positive emotions. Issue 2 (17th February 2018) - Aragón, Oriana R.; Bargh, John A.
ABSTRACT: Happiness can be expressed through smiles. Happiness can also be expressed through physical displays that without context, would appear to be sadness (tears, downward turned mouths, and crumpled body postures) and anger (clenched jaws, snarled lips, furrowed brows, and pumped fists). These seemingly incongruent displays of happiness, termed dimorphous expressions, we propose, represent and communicate expressers' motivational orientations. When participants reported their own aggressive expressions in positive or negative contexts, their expressions represented positive or negative emotional experiences respectively, imbued with appetitive orientations (feelings of wanting to go). In contrast, reported sad expressions, in positive or negative contexts, represented positive and negative emotional experiences respectively, imbued with consummatory orientations (feelings of wanting to pause). In six additional experiments, participant observers interpreted that aggression displayed in positive contexts signalled happy-appetitive states, and sadness displayed in positive contexts signalled happy-consummatory states. Implications for the production and interpretation of emotion expressions are discussed.